Mongol nomádok ma: az akkulturáció kérdése a mobilitásvesztés okainak és hatásainak tükrében - Éliás, Boglárka Anna (Távol-keleti Tanulmányok, 2018)
We are witnessing changes to the Mongolian nomad social system: globalisation, political, economic and climatic changes are all affecting traditional pastoral nomadism. The mobility of the Mongolian nomads drastically decreased in the last twenty years. Some researchers argue that the mobility change will accelerate the acculturation of Mongolian pastoral nomads. Based on my fieldwork and research, I consider the issue of acculturation a very complex phenomenon, which depends on the adaptiveness and flexibility of the nomads. For this reason, we should look at these specific aspects of the Mongolian nomadic pastoralism. In this study, I present the historical, economic and ecological reasons for the mobility decrease and the theoretical background of my fieldwork.